A multi-perspective view of genetic variation in Cameroon. - Coia, V; Brisighelli, F; Donati, F; Pascali, V; Boschi, I; Luiselli, D; Battaggia, C; Batini, C; Taglioli, L; Cruciani, F; Paoli, G; Capelli, C; et al. (2009)
In this study, we report the genetic variation of autosomal and Y-chromosomal microsatellites in a large Cameroon population dataset (a total of 11 populations) and jointly analyze novel and previous genetic data (mitochondrial DNA and protein coding loci) taking geographic and cultural factors into consideration. The complex pattern of genetic variation of Cameroon can in part be described by contrasting two geographic areas (corresponding to the northern and southern part of the country), which differ substantially in environmental, biological, and cultural aspects. Northern Cameroon populations show a greater within- and among-group diversity, a finding that reflects the complex migratory patterns and the linguistic heterogeneity of this area. A striking reduction of Y-chromosomal genetic diversity was observed in some populations of the northern part of the country (Podokwo and Uldeme), a result that seems to be related to their demographic history rather than to sampling issues. By exploring patterns of genetic, geographic, and linguistic variation, we detect a preferential correlation between genetics and geography for mtDNA. This finding could reflect a female matrimonial mobility that is less constrained by linguistic factors than in males. Finally, we apply the island model to mitochondrial and Y-chromosomal data and obtain a female-to-male migration Nnu ratio that was more than double in the northern part of the country. The combined effect of the propensity to inter-populational admixture of females, favored by cultural contacts, and of genetic drift acting on Y-chromosomal diversity could account for the peculiar genetic pattern observed in northern Cameroon.